2017
DOI: 10.1103/physrevlett.119.035001
|View full text |Cite
|
Sign up to set email alerts
|

Noninductively Driven Tokamak Plasmas at Near-Unity Toroidal Beta

Abstract: Access to and characterization of sustained, toroidally confined plasmas with a very high plasma-to-magnetic pressure ratio (β_{t}), low internal inductance, high elongation, and nonsolenoidal current drive is a central goal of present tokamak plasma research. Stable access to this desirable parameter space is demonstrated in plasmas with ultralow aspect ratio and high elongation. Local helicity injection provides nonsolenoidal sustainment, low internal inductance, and ion heating. Equilibrium analyses indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…An alternate possibility is suggested by equilibrium reconstructions of LHI plasmas, which suggest a possible relationship between the formation of a minimum |B| well and the trans ition to the reduced n = 1 regime. LHI discharges at low B T often contain large regions of absolute minimum |B| resulting from the hollow current profiles of LHI plasmas and the ultra-low aspect ratio of Pegasus [28]. A study of model equilibria showed that the formation of a |B| well in Pegasus is strongly influenced by I p /I TF , with large values being favorable for well formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate possibility is suggested by equilibrium reconstructions of LHI plasmas, which suggest a possible relationship between the formation of a minimum |B| well and the trans ition to the reduced n = 1 regime. LHI discharges at low B T often contain large regions of absolute minimum |B| resulting from the hollow current profiles of LHI plasmas and the ultra-low aspect ratio of Pegasus [28]. A study of model equilibria showed that the formation of a |B| well in Pegasus is strongly influenced by I p /I TF , with large values being favorable for well formation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ohmically-driven plasmas in Pegasus are limited to I p /I TF 1.3 [27]. LHI plasmas at very low B T ( I TF 56 kA, I p /I TF ∼ 2) have been shown to access β T ∼ 100% [28].…”
Section: The Hfs Lhi Operating Spacementioning
confidence: 99%
“…Non-inductively driven plasmas at low access world-record ~ 100%, high ~ 6.5 and feature an absolute minimum-| | magnetic configuration (Fig. 13) that may positively affect turbulence, transport, and fast particle confinement [23]. Discharges at highest disrupt at the ideal no-wall MHD limit.…”
Section: Advancing Lhi Physics Understandingmentioning
confidence: 99%
“…Access to the reduced MHD state also facilitates access to the favorable low-A ST regime with non-solenoidal sustainment, high κ, low i , and high β t [39]. Non-inductively driven plasmas at low B T access world-record β t ~ 100%, high β N ~ 6.5 and feature an absolute minimum-|B| magnetic configuration (figure 20) that may positively affect turbulence, transport, and fast particle confinement [10,40]. Discharges at highest β t disrupt at the ideal no-wall MHD limit.…”
Section: Advancing Lhi Physics Understandingmentioning
confidence: 99%
“…In the last three decades of ST research, various CS-free plasma startup scenarios were proposed such as merging compression (MC) [4], local helicity injection [5], electron Bernstein wave plasma startup [3] and so on. The former two explore high beta records [6][7][8] and H-mode performance [9] in mega ampere (MA) scale experiments [1,4,10], while the latter explores long pulse steady scenario which has longer duration time than 100 ms [1,3]. In addition to the initial current formation method, merging plasma startup scheme is known that it also enables the advantage of impulsive MW scale plasma heating during plasma formation through magnetic reconnection process [4,11].…”
Section: Introductionmentioning
confidence: 99%